Supporting Risk Management in Finance through the Use of ICT. A Systematic Literature Review - Chomiak-Orsa, Iwona; Greńczuk, Andrzej; Łuczak, Kamila (Wspomaganie zarządzania ryzykiem w finansach poprzez wykorzystanie ICT. Systematyczny przegląd literatury, 2022)
Risk management is a function performed in every enterprise. However, it plays a particularly important role in organizations from the financial industry. Currently, there are many ICT tools available on the market that facilitate the risk management process in companies. The authors examined the following research problem, namely the tendency of the use of ICT in financial risk management described in the literature. The aim was to show the relation between risk management in finance and ICT tools in the literature. The research method was a statistical systematic literature review which covered five databases: Scopus, Web of Science, IEEE Xplore, ScienceDirect and Google Scholar, over the period from 2010 to 2021.
Informatyka Ekonomiczna = Business Informatics, 2022, Nr 2 (64), s. 1-9
Keywords: ICT; literature review; finances; risk management; przegląd literatury; finanse; zarządzanie ryzykiem